Ága [videorecording (DVD)] - Aprosimov, Mikhail; Ivanova, Feodosia; Tikhonova, Galina, 1987- (Big World Pictures, 2020)
In a yurt on the snow-covered fields of the North, Nanook and Sedna live following the traditions of their ancestors. Hunting becomes more and more difficult, the animals around them die from inexplicable causes, and the ice has been melting every year. Chena, who visits them regularly, is their only connection to their daughter Aga, who left the icy tundra long ago due to a family feud. When Sedna's health deteriorates, Nanook embarks on a long journey in order to find Aga.